2005
DOI: 10.1080/13811110590512822
|View full text |Cite
|
Sign up to set email alerts
|

How Effective is Advanced Training Concerning Depression and Suicidality among the Elderly? Results of a Pilot Study

Abstract: Three Hundred and Seventy Four geriatric caregivers in Nuremberg and Munich participated in a four-hour advanced in-house training addressing the topic. "depression and suicidality in old age." Geriatric caregivers are key persons in early diagnosis of depressive symptoms and suicidality. The training focused on qualifying and sensitizing caregivers for these topics. A 12-item questionnaire was applied to measure the outcome parameters "knowledge and attitudes towards depression and suicidality in old age" wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
1
16
0
2
Order By: Relevance
“…Ziervogel et al . () reported similar results in a training session about knowledge and attitudes toward depression and suicide for caregivers. In a study evaluating ability to recognize risk factors for suicide and indirect suicidal behavior among clinical psychologists who work with older adults, providers were generally able to identify clinical risk factors (e.g., history of suicide attempt, depression, hopelessness, social isolation) but failed to recognize many others, such as bereavement, male gender, presence of medical illness, marital status, and ethnicity (Brown et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Ziervogel et al . () reported similar results in a training session about knowledge and attitudes toward depression and suicide for caregivers. In a study evaluating ability to recognize risk factors for suicide and indirect suicidal behavior among clinical psychologists who work with older adults, providers were generally able to identify clinical risk factors (e.g., history of suicide attempt, depression, hopelessness, social isolation) but failed to recognize many others, such as bereavement, male gender, presence of medical illness, marital status, and ethnicity (Brown et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Several studies have trialed educational interventions for nursing staff to improve detection rates of depression in elderly nursing home residents (Walker and Osgood, 2000;Cuijpers and van Lammeren, 2001;Moxon et al, 2001;Rosen et al, 2002;Boyle et al, 2004;Mayall et al, 2004;Eissis et al, 2005). While there were indications that training on understanding depression and in the use of screening tools may increase staff knowledge and confidence (Walker and Osgood, 2000;Moxon et al, 2001;Boyle et al, 2004;Eissis et al, 2005;Ziervogel et al, 2005), increasing knowledge of depression or training in the use of validated screening tools alone may be insufficient to increase the detection and treatment of depression. Previous research has indicated that low self-efficacy and carers' perceived barriers to care, such as time constraints and poor communication, may lead to lower detection rates of depression in older people (McCabe et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Training in suicide prevention should involve not only knowledge acquisition (e.g., the assessment and management of suicide risk), but also a change in attitudes toward suicidal behavior. The ability of brief educational intervention programs to change attitudes of healthcare professionals toward suicide has been examined by measuring pre‐and post‐training attitudes in the short‐term (Appleby et al, 2000; Morriss, Gask, Battersby, Francheschini, & Robson, 1999; Samuelsson & Asberg, 2002; Ziervogel, Pfeiffer, & Hegerl, 2005). Although overall improvement of attitudes have been achieved, how long this change is maintained remains unanswered.…”
mentioning
confidence: 99%